Population Pharmacokinetics of Intramuscular Artesunate in African Children With Severe Malaria: Implications for a Practical Dosing Regimen. Issue 5 (8th February 2013) - Hendriksen, ICE; Mtove, G; Kent, A; Gesase, S; Reyburn, H; Lemnge, M M; Lindegardh, N; Day, N P J; von Seidlein, L; White, N J; Dondorp, A M; Tarning, J
<x xml:space="preserve">Abstract</x> Parenteral artesunate (ARS) is the drug of choice for the treatment of severe malaria. Pharmacokinetics data on intramuscular ARS are limited with respect to the main treatment group that carries the highest mortality, namely, critically ill children with severe malaria. A population pharmacokinetic study of ARS and dihydroartemisinin (DHA) was conducted from sparse sampling in 70 Tanzanian children of ages 6 months to 11 years. All the children had been admitted with severe falciparum malaria and were treated with intramuscular ARS (2.4 mg/kg at 0, 12, and 24 h). Venous plasma concentration–time profiles were characterized using nonlinear mixed‐effects modeling (NONMEM). A one‐compartment disposition model accurately described first‐dose population pharmacokinetics of ARS and DHA. Body weight significantly affected clearance and apparent volume of distribution (P < 0.001), resulting in lower ARS and DHA exposure levels in smaller children. An adapted dosing regimen including a practical dosing table per weight band is proposed for young children based on the pharmacokinetic model. Clinical Pharmacology & Therapeutics (2013); 93 5, 443–450. doi:10.1038/clpt.2013.26